Beyond School Contact: Two-Way Teacher–Parent Communication and Parental Involvement in Islamic Early Childhood Education - Nuraini, Febritesna; Saryono, Djoko; Latif, Abdul; Zain, Azizah Binti; Ishaq, M.; Sudarsono, Bambang; Supriyanto, Agus (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study examines whether two-way teacher–parent communication is associated with parental involvement in Islamic early childhood education institutions. It addresses the limited empirical attention given to two-way communication as a distinct relational construct within faith-based early childhood education.Design/methods/approach – The study employed a quantitative correlational design. Data were collected from 175 valid parent responses drawn from Islamic early childhood education institutions in Yogyakarta City, most of which were part of the ’Aisyiyah Bustanul Athfal kindergarten network. The data were analyzed using descriptive statistics and simple linear regression.Findings – The results show a statistically significant positive association between two-way teacher–parent communication and parental involvement. higher levels of reciprocal and responsive communication were associated with higher reported parental involvement. The coefficient of determination (R² = 0.294) indicates that two-way teacher–parent communication explained a moderate proportion of the variance in parental involvement, while a substantial proportion remained attributable to factors outside the model.Research implications/limitations – The study contributes to the literature by treating two-way communication as a specific interactional construct rather than a general background dimension of school–family relations. However, the cross -sectional correlational design, reliance on self-reported data, and focus on a single urban context limit causal inference and broader generalizability.Practical implications – The findings highlight the need for early childhood institutions, particularly in culturally embedded and resource-constrained contexts, to shift from one-way information delivery to dialogic, responsive communication. In Islamic early childhood settings, culturally aligned and relational communication practices can strengthen sustained parental engagement through interactive and trust-based partnerships.Originality/value – This study contributes to Global South scholarship by providing empirical evidence from Islamic early childhood education in Indonesia, a context underrepresented in the literature. It advances the field by conceptualizing two-way communication as a distinct dialogic and relational construct, offering a context-sensitive perspective that challenges dominant Western-centric models of family–school partnerships.Paper type Research paper